Nomadyczność wieloznaczna, wieloznaczność nomadyczna, czyli o wzorach osobowości Zygmunta Baumana - Mróz, Tomasz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
In this article, author deals the subject of Zygmunt Bauman’s four patterns of personality as an attribute of postmodern people. This analysis aims to check if the shared qualities of the personality models might have emerged in the past. A certain type of individuals, which is resulting from Bauman’s patterns, needs a reference to the conception of societies that are provided by the research of Guy Debord, Michel Foucault and Michel de Certeau. This comparison makes it possible to verify the validity of the patterns, as well as answer the question, if they are a diagnosis of the culture, or rather a speculation, that is out of touch with reality.